Method for producing zinc-containing substance, method for producing electrogalvanizing bath, and method for producing electrogalvanized steel sheet

By controlling the pH value of ironmaking dust and acidic aqueous solution and adding chelating agents, impurity metals are precipitated, solving the appearance quality problem in the zinc recovery process from ironmaking dust, and realizing the manufacture of beautiful and bright electro-galvanized steel sheets.

CN120858189APending Publication Date: 2025-10-28JFE STEEL CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202480017914.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-13
Filing Date
2024-03-11
Publication Date
2025-10-28

AI Technical Summary

Technical Problem

In the prior art, when zinc is recovered from ironmaking dust as raw material for electrogalvanized steel sheets, the appearance quality of the zinc is affected by impurity metals, causing the plated surface to become black and failing to meet the requirements for a beautiful and bright appearance.

Method used

By contacting ironmaking dust with an acidic aqueous solution to leach zinc, the pH value of the treatment solution is controlled within a specific range. A chelating agent is added to precipitate impurity metals, and solid-liquid separation is performed to obtain zinc-containing material free of impurities. This material is then used in an electroplating zinc bath, and the pH value of the electroplating zinc bath is controlled to manufacture electroplated zinc steel sheets.

Benefits of technology

This technology enables the production of electro-galvanized steel sheets with a beautiful and bright appearance using iron smelting dust as raw material, thereby improving zinc recovery rate and coating quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120858189A_ABST
    Figure CN120858189A_ABST
Patent Text Reader

Abstract

Provided is a zinc-containing substance which can be used for producing an electrogalvanized steel sheet having a beautiful and bright appearance. The method comprises: a zinc leaching step in which iron-making dust is brought into contact with an acidic aqueous solution to leach zinc contained in the iron-making dust into the acidic aqueous solution; a first impurity precipitation step in which impurities are precipitated in a state in which the pH of the first treatment liquid obtained in the zinc leaching step is 4.0-6.0; a second impurity precipitation step for adding 0.10 g / L or more of a chelating agent to the second treatment liquid obtained in the first impurity precipitation step in a pH of 4.0-6.0 to precipitate impurities; a first solid-liquid separation step for performing solid-liquid separation on the third treatment liquid obtained in the second impurity precipitation step; a zinc precipitation step in which a zinc-containing substance is precipitated in a state in which the fourth treatment liquid obtained in the first solid-liquid separation step has a pH of 8.0-12.0; and a second solid-liquid separation step for separating the fifth treated liquid obtained in the zinc precipitation step into a zinc-containing substance and a raffinate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to methods for preparing zinc-containing substances, methods for preparing electro-galvanizing baths, and methods for manufacturing electro-galvanized steel sheets. Background Technology

[0002] Zinc, as a representative base metal, is used in a wide variety of industries. Particularly in the steel industry, zinc exhibits excellent corrosion resistance due to its low potential relative to iron, providing sacrificial corrosion protection. Therefore, zinc is widely used as a coating material for steel sheets in automotive, home appliance, and building materials applications.

[0003] Common methods for manufacturing galvanized steel sheets include hot-dip galvanizing, which forms a zinc coating on the steel sheet surface by immersing it in a hot-dip galvanizing bath, and electroplating, which immerses the steel sheet in an acidic solution containing zinc ions and deposits a zinc coating on the steel sheet surface through an electrochemical reaction. Both methods typically use metallic zinc as the raw material. However, in recent years, with the rise of emerging countries, the supply and demand balance has changed, leading to an increase in the price of metallic zinc.

[0004] In such cases, attempts are being made to separate and recover industrial waste and ironmaking byproducts composed of other metals containing zinc as a zinc source, replacing metallic zinc. For example, ironmaking dust such as blast furnace dust, converter dust, and electric furnace dust contains zinc from galvanized steel scrap and iron ore. Therefore, technologies for recovering and separating zinc from ironmaking dust as a zinc source have been reported. For example, Patent Document 1 describes a method that separates ironmaking dust into coarse and fine dust particles, contacts the fine dust with acid to leach zinc into the acid, and then recovers the zinc by repeatedly adding alkali and performing solid-liquid separation.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2022-105980 Summary of the Invention

[0008] In galvanized steel sheets, electro-galvanized steel sheets are typically used directly without coating after chemical conversion treatment, requiring excellent surface appearance. Whiteness is a crucial factor, usually expressed as brightness (L value). The inventors' research indicates that when zinc recovered from ironmaking dust using the method described in Patent Document 1 is used as the zinc raw material for the electro-galvanizing bath, the L value of the plated surface decreases due to the influence of impurity metals (e.g., Pb, Cd) believed to originate from ironmaking dust, resulting in a darker appearance compared to conventional electro-galvanized steel sheets. Therefore, when using zinc-containing materials derived from ironmaking dust using the method described in Patent Document 1 to manufacture electro-galvanized steel sheets, the desired appearance cannot be obtained.

[0009] Therefore, the object of the present invention is to provide a zinc-containing material made from iron smelting dust that can be used to manufacture electro-galvanized steel sheets with a beautiful and bright appearance.

[0010] The inventors conducted in-depth research on methods to solve the aforementioned problems. Their findings revealed that by contacting iron smelting dust with an acidic aqueous solution, the zinc contained in the iron smelting dust is leached into the acidic aqueous solution. After the pH of the resulting treatment solution (first treatment solution) reaches 4.0–6.0, a predetermined amount of chelating agent is added to the resulting treatment solution (second treatment solution). This maintains the zinc concentration in the treatment solution while allowing impurity metals to precipitate as hydroxides and chelates. Furthermore, after solid-liquid separation of the resulting treatment solution (third treatment solution), the pH of the resulting treatment solution (fourth treatment solution) is adjusted to 8.0–12.0, and then solid-liquid separation is performed again on the resulting treatment solution (fifth treatment solution), thereby obtaining a zinc-containing substance free of impurity metals. Moreover, the inventors discovered that by using the obtained zinc-containing substance as a zinc source in the electroplating zinc process, electroplated galvanized steel sheets with a beautiful and bright appearance can be manufactured, thus completing this invention.

[0011] That is, the essence of the present invention is as follows.

[0012] [1] A method for producing a zinc-containing substance, characterized by comprising the following steps:

[0013] In the zinc leaching process, iron smelting dust is brought into contact with an acidic aqueous solution, so that the zinc contained in the iron smelting dust is leached into the acidic aqueous solution.

[0014] In the first impurity precipitation step, impurities are precipitated when the pH of the first treatment solution obtained in the zinc leaching step is 4.0 to 6.0.

[0015] In the second impurity precipitation step, a chelating agent of 0.10 g / L or more is added to the second processed solution obtained in the first impurity precipitation step at a pH of 4.0 to 6.0 to precipitate the impurities.

[0016] The first solid-liquid separation process involves performing solid-liquid separation on the third processed liquid obtained in the second impurity precipitation process.

[0017] In the zinc precipitation process, zinc-containing substances are precipitated in the fourth treatment solution obtained in the first solid-liquid separation process at a pH of 8.0 to 12.0; and

[0018] The second solid-liquid separation process separates the fifth treatment liquid obtained in the zinc precipitation process into zinc-containing substances and residual liquid.

[0019] [2] According to the method for producing zinc-containing substances described in [1] above, in the pre-process of zinc leaching, a grading process is further included to separate iron smelting dust into coarse dust and fine dust, and the fine dust obtained in the grading process is used as the iron smelting dust used in the zinc leaching process.

[0020] [3] According to the method for producing zinc-containing substances described in [1] or [2] above, in the second impurity precipitation step above, at least one of the chelating agents added to the second treatment liquid above is a chelating agent that forms a chelate with at least one of Cd and Pb.

[0021] [4] The method for producing a zinc-containing substance according to any one of [1] to [3] above, wherein, in the second impurity precipitation step above, at least one of the chelating agents added to the second treatment liquid above is a compound having the structure shown in the following general formula (I). Wherein, R 1 and R 2 M indicates a substituted alkyl group. + It represents a monovalent cation.

[0022]

[0023] [5] A method for preparing an electroplating zinc bath, characterized in that the electroplating zinc bath contains a zinc-containing substance prepared by any one of the zinc-containing substances described in [1] to [4] above, and the pH of the electroplating zinc bath is 0.5 to 3.5.

[0024] [6] A method for manufacturing an electro-galvanized steel sheet, characterized in that an electro-galvanizing bath prepared by the method described in [5] above is used to electro-galvanize the surface of the steel sheet, thereby manufacturing an electro-galvanized steel sheet.

[0025] According to the present invention, a zinc-containing material made from iron smelting dust can be provided for use in manufacturing electroplated galvanized steel sheets with a beautiful and bright appearance. Attached Figure Description

[0026] Figure 1This is a flowchart illustrating an example of a method for preparing a zinc-containing substance according to the present invention.

[0027] Figure 2 This is a flowchart illustrating a preferred example of a method for preparing a zinc-containing substance according to the present invention. Detailed Implementation

[0028] (Methods for preparing zinc-containing substances)

[0029] The embodiments of the present invention will now be described. It should be noted that the present invention is not limited to the following embodiments. Furthermore, in this specification, the numerical range indicated by “~” refers to the range including the values ​​described before and after “~” as both the lower and upper limits.

[0030] Figure 1 The diagram shows a process flow of an example of a method for preparing the zinc-containing substance according to the present invention. The method for producing the zinc-containing substance of the present invention is characterized by comprising the following steps: a zinc leaching step (step S1), in which iron smelting dust is contacted with an acidic aqueous solution to leach zinc contained in the iron smelting dust into the acidic aqueous solution; a first impurity precipitation step (step S2), in which impurities are precipitated at a pH of 4.0 to 6.0 in the first treatment solution obtained in the zinc leaching step; a second impurity precipitation step (step S3), in which a chelating agent of 0.10 g / L or more is added to the second treatment solution obtained in the first impurity precipitation step at a pH of 4.0 to 6.0 to precipitate impurities; a first solid-liquid separation step (step S4), in which the third treatment solution obtained in the second impurity precipitation step is subjected to solid-liquid separation; a zinc precipitation step (step S5), in which the zinc-containing substance is precipitated at a pH of 8.0 to 12.0 in the fourth treatment solution obtained in the first solid-liquid separation step; and a second solid-liquid separation step (step S6), in which the fifth treatment solution obtained in the zinc precipitation step is separated into zinc-containing substance and residue.

[0031] <Zinc Leaching Process>

[0032] First, in step S1, the ironmaking dust is brought into contact with an acidic aqueous solution, so that the zinc contained in the ironmaking dust is leached into the acidic aqueous solution (zinc leaching process).

[0033] Ironmaking dust used as raw materials can include blast furnace dust, converter dust, electric furnace dust, etc.

[0034] As the acidic aqueous solution used in this zinc leaching process, general acidic aqueous solutions such as sulfuric acid and hydrochloric acid can be used. It should be noted that, from the viewpoint of using the ultimately recovered zinc-containing material in the zinc plating bath, it is preferable to use an acid containing anions of the same type as the zinc plating bath used. When using a sulfuric acid bath as the zinc plating bath, sulfuric acid is preferred as the acidic aqueous solution; when using a chloride bath as the zinc plating bath, hydrochloric acid is preferred as the acidic aqueous solution.

[0035] There is no particular lower limit to the pH of the acidic aqueous solution used for zinc leaching, but if the pH is below 1.0, the consumption of reagents increases, and the processing cost increases. Therefore, the pH of the acidic aqueous solution used for zinc leaching is preferably 1.0 or higher, more preferably 2.0 or higher. On the other hand, if the pH of the acidic aqueous solution used for zinc leaching is higher than 5.0, zinc is difficult to leach, and zinc cannot be effectively recovered. Therefore, the pH of the acidic aqueous solution used for zinc leaching is preferably 5.0 or lower, more preferably 4.0 or lower, and even more preferably 3.5 or lower.

[0036] Furthermore, the zinc leaching time is preferably 10 minutes or more. By setting the zinc leaching time to 10 minutes or more, zinc can be fully leached into the acidic aqueous solution, thus effectively recovering the zinc. On the other hand, there is no particular upper limit to the zinc leaching time, but to avoid prolonging the processing time, it is preferable to set it to 120 minutes or less.

[0037] It should be noted that the reaction temperature during zinc leaching can be arbitrarily set within the temperature range where the acidic aqueous solution will not solidify or evaporate. Considering temperature stability, the reaction temperature during zinc leaching is preferably above 30°C. If the temperature is too high, the evaporation rate of the acidic aqueous solution will increase; therefore, it is preferably below 90°C. Furthermore, it is preferable to stir the acidic aqueous solution during the leaching process. The method of stirring the acidic aqueous solution is not particularly limited; for example, methods using a stir bar mixer, a propeller mixer, or a pump can be cited.

[0038] <First Impurity Precipitation Process>

[0039] Next, in step S2, impurities are precipitated in the first treatment solution obtained in the zinc leaching process at a pH of 4.0 to 6.0 (first impurity precipitation step).

[0040] It can be assumed that the first treatment solution obtained in the zinc leaching process inevitably contains impurities in the form of metal ions, which are leached from ironmaking dust into the acidic aqueous solution along with zinc. Furthermore, it is believed that these impurities precipitate onto the steel sheet along with zinc during electroplating, thus reducing the L-value of the galvanized steel sheet. Therefore, to obtain electroplated galvanized steel sheets with a beautiful and bright appearance, it is crucial to reduce these impurities. On the other hand, if zinc also precipitates during impurity precipitation, the resource reuse rate as a galvanizing raw material will also decrease. Therefore, it is necessary to precipitate impurities while maintaining the zinc concentration contained in the aforementioned first treatment solution.

[0041] The inventors conducted in-depth research on the conditions for separating and precipitating impurities while maintaining the zinc concentration in the first treatment solution. The results showed that by setting the pH of the first treatment solution to 4.0–6.0 (first impurity precipitation step), adding a predetermined amount of chelating agent to the resulting treatment solution (second treatment solution) to precipitate impurities (second impurity precipitation step), impurity elements other than zinc can precipitate as hydroxides and chelates. After solid-liquid separation of the resulting treatment solution (third treatment solution) (first solid-liquid separation step), and then setting the pH of the resulting treatment solution (fourth treatment solution) to 8.0–12.0, followed by solid-liquid separation of the resulting treatment solution (fifth treatment solution) (second solid-liquid separation step), a zinc-containing substance free of impurity metals can be obtained. Therefore, a zinc-containing substance suitable for manufacturing electroplated galvanized steel sheets with a beautiful and bright appearance can be obtained.

[0042] Therefore, in this first impurity precipitation step, by maintaining the pH of the first treatment solution obtained in the zinc leaching step at 4.0 to 6.0, impurities (mainly Fe) are precipitated as hydroxides while maintaining the zinc concentration in the first treatment solution. By maintaining the pH of the first treatment solution at 4.0 or higher, Fe can be precipitated efficiently; therefore, the pH of the first treatment solution is set to 4.0 or higher. The lower limit of the pH of the first treatment solution is preferably 4.3, more preferably 4.5. Furthermore, by maintaining the pH of the first treatment solution at 6.0 or lower, zinc precipitation can be suppressed, the zinc concentration in the solution can be maintained, and zinc can be effectively recovered; therefore, the pH of the first treatment solution is set to 6.0 or lower. The upper limit of the pH of the first treatment solution is preferably 5.8, more preferably 5.5.

[0043] When the pH of the first treatment solution obtained in the zinc leaching process is less than 4.0, it is necessary to adjust the pH of the first treatment solution to 4.0 to 6.0. Methods for adjusting the pH include, for example, adding common alkaline aqueous solutions such as sodium hydroxide or calcium hydroxide. Conversely, when the pH of the first treatment solution obtained in the zinc leaching process is within the range of 4.0 to 6.0, pH adjustment may not be necessary.

[0044] The temperature of the first processing solution in the first impurity precipitation step can be arbitrarily set within the temperature range where the first processing solution does not solidify or evaporate. Considering temperature stability, the temperature of the first processing solution is preferably 30°C or higher. If the temperature is too high, the evaporation rate of the first processing solution will increase, so it is preferably below 90°C. Furthermore, considering the precipitation time and processing efficiency of impurities, the reaction time of the first impurity precipitation step is preferably 10 to 120 minutes.

[0045] <Second Impurity Precipitation Process>

[0046] Next, in step S3, a chelating agent of 0.10 g / L or more is added to the second treatment solution obtained in the first impurity precipitation step at a pH of 4.0 to 6.0 to precipitate the impurities (second impurity precipitation step).

[0047] The first impurity precipitation step allows some impurities (mainly Fe) to precipitate as hydroxides, but heavy metals such as Cd and Pb do not precipitate and remain in the solution. Therefore, in the second impurity precipitation step, a chelating agent is added to the second treated solution obtained in the first impurity precipitation step, causing heavy metals such as Cd and Pb to precipitate as chelates.

[0048] For the above purposes, in the second impurity precipitation step, at least one of the chelating agents added to the second treatment solution is preferably a chelating agent that forms a chelate with at least one of Cd and Pb. By using such a chelating agent, heavy metal elements such as Cd and Pb can be efficiently precipitated as chelates.

[0049] In this invention, in the second impurity precipitation step, at least one chelating agent added to the second treatment liquid is more preferably a compound having the structure shown in general formula (I). Wherein, R 1 and R 2 This indicates a substituted alkyl group. Additionally, M... + This indicates a monovalent cation, such as a proton, alkali metal ion, or ammonium ion. It should be noted that a compound may contain more than two structures represented by general formula (I).

[0050]

[0051] The structure represented by the above general formula (I) is considered to easily form stable complexes with heavy metal elements such as Cd and Pb because the compound contains a total of three nitrogen and sulfur atoms with lone pairs of electrons required for coordination with metals.

[0052] Examples of compounds with this structure include dimethyl dithiocarbamates, diethyl dithiocarbamates, piperazine-1,4-dithiocarbamate dipotassium salt, diethylamine-N-dithiocarbamate potassium salt, and pyrrolidine-1-dithiocarbamate ammonium salt.

[0053] Furthermore, the amount of chelating agent added to the second treatment solution is preferably 0.10 g / L or more to sufficiently reduce impurity elements. More preferably, the amount of chelating agent added is 0.20 g / L or more, and even more preferably 0.50 g / L or more. There is no particular upper limit to the amount of chelating agent added, but from the viewpoint of treatment cost, it is preferably 5.00 g / L or less.

[0054] In the second impurity precipitation step, a chelating agent is added to the second processed solution obtained in the first impurity precipitation step at a pH of 4.0 to 6.0. By ensuring that the pH of the second processed solution at the time of chelating agent addition is 4.0 or higher, the decomposition of the chelating agent added in the second impurity precipitation step can be suppressed, allowing it to stably form complexes with heavy metal elements and efficiently remove them. The lower limit of the pH of the second processed solution is preferably 4.3, and more preferably 4.5. Furthermore, when the pH exceeds 6.0, zinc precipitates, the zinc concentration in the solution decreases, and the zinc recovery rate also decreases; therefore, the pH of the second processed solution needs to be maintained below 6.0. The upper limit of the pH of the second processed solution is preferably 5.8, and more preferably 5.5.

[0055] The pH of the second treatment solution obtained in the first impurity precipitation step is preferably maintained at 4.0 to 6.0 before the addition of the chelating agent. As mentioned above, the pH of the second treatment solution needs to be maintained below 6.0, but as long as the pH is 4.0 to 6.0 when the chelating agent is added, the pH of the second treatment solution can be temporarily lower than 4.0.

[0056] Furthermore, the reaction time for the second impurity precipitation step is preferably 10 minutes or more. By setting the reaction time to 10 minutes or more, the impurities contained in the second treatment solution can be sufficiently precipitated. There is no particular upper limit to the reaction time, but to avoid prolonging the treatment time, it is preferably 120 minutes or less. It should be noted that the temperature of the second treatment solution in the second impurity precipitation step can be arbitrarily set within the temperature range where the second treatment solution will not solidify or evaporate. Considering temperature stability, the temperature of the second treatment solution is preferably 30°C or higher; if the temperature is too high, the evaporation rate of the second treatment solution will increase, therefore, 90°C or lower is preferred.

[0057] <First Solid-Liquid Separation Process>

[0058] Next, in step S4, the third processing liquid obtained in the second impurity precipitation step is subjected to solid-liquid separation (first solid-liquid separation step).

[0059] This solid-liquid separation process separates the third processed liquid obtained in the second impurity precipitation process into precipitated solid components (hydroxides and chelates of impurities) and the fourth processed liquid. The method of solid-liquid separation is not particularly limited; for example, gravity sedimentation, filtration, centrifugation, filter press, or any other method can be used.

[0060] <Zinc Precipitation Process>

[0061] Then, in step S5, the zinc-containing substance is precipitated in the fourth processing liquid obtained in the first solid-liquid separation step at a pH of 8.0 to 12.0 (zinc precipitation step).

[0062] Therefore, in this process, by setting the pH of the fourth processing solution obtained in the first solid-liquid separation process to 8.0 to 12.0, the zinc contained in the fourth processing solution is precipitated as a zinc-containing substance. By setting the pH of the fourth processing solution to 8.0 or higher, zinc can be precipitated efficiently; therefore, the pH of the fourth processing solution is set to 8.0 or higher. The lower limit of the pH of the fourth processing solution is preferably 8.3, more preferably 8.5. Furthermore, by setting the pH of the fourth processing solution to 12.0 or lower, zinc redissolution can be suppressed; therefore, the pH of the fourth processing solution is set to 12.0 or lower. The upper limit of the pH of the fourth processing solution is preferably 11.8, more preferably 11.5.

[0063] When the pH of the fourth processed liquid obtained in the first solid-liquid separation step is less than 8.0, it is necessary to adjust the pH of the fourth processed liquid to 8.0 to 12.0. Methods for adjusting the pH include, for example, adding a common alkaline aqueous solution such as sodium hydroxide or calcium hydroxide. On the other hand, when the pH of the fourth processed liquid obtained in the first solid-liquid separation step is within the range of 8.0 to 12.0, pH adjustment is not required.

[0064] The temperature of the fourth processing solution in the zinc precipitation process can be arbitrarily set within the temperature range where the fourth processing solution will not solidify or evaporate. Considering temperature stability, the temperature of the fourth processing solution is preferably 30°C or higher. On the other hand, if the temperature of the fourth processing solution becomes too high, the evaporation rate of the fourth processing solution will increase. Therefore, the temperature of the fourth processing solution is preferably 90°C or lower. Furthermore, considering the precipitation time of impurities and processing efficiency, the reaction time of the zinc precipitation process is preferably 10 to 120 minutes.

[0065] <Second solid-liquid separation process>

[0066] Finally, in step S6, the fifth processing liquid obtained in the zinc precipitation process is separated into solid and liquid phases and recovered (second solid-liquid separation process).

[0067] The second solid-liquid separation step separates the fifth treatment solution obtained in the zinc precipitation step into zinc-containing substances and residual liquid. The method of solid-liquid separation is not particularly limited; for example, gravity sedimentation, filtration, centrifugation, filter press, or any other method can be used. It should be noted that since the zinc-containing substances obtained in the second solid-liquid separation step contain water, a drying treatment can be added as needed at the end of the second solid-liquid separation step.

[0068] This allows zinc-containing substances to be produced from iron smelting dust.

[0069] It should be noted that in this invention, zinc recovery rate refers to the ratio, expressed as a percentage, of the amount of zinc contained in zinc-containing substances to the amount of zinc contained in ironmaking dust. From the viewpoint of processing costs, a zinc recovery rate of 10% by mass or more is preferred, and more preferably 20% by mass or more.

[0070] The zinc-containing material obtained according to the present invention can be used as part of an electroplating zinc bath. Additionally, it can be used as part of a plating bath during Fe-Zn electroplating, Ni-Zn electroplating, and other zinc-containing metal electroplating processes, and can also be used to manufacture electroplated steel sheets with these plating layers on at least one side.

[0071] <Grading Process>

[0072] Figure 2 The flowchart illustrates a preferred example of a method for preparing the zinc-containing substance according to the present invention. For example... Figure 2 As shown, in the present invention, in step S7, the initial stage of the zinc leaching process, it is preferable to separate the iron smelting dust into coarse dust and fine dust (grading process). Furthermore, the fine dust obtained in this grading process is preferably used as the iron smelting dust in the zinc leaching process, the subsequent stage of this grading process.

[0073] Zinc volatilized during the ironmaking process typically exists as fine particles around a few micrometers in size and tends to be less dense than iron. Therefore, fine dust contains more zinc than coarse dust. Furthermore, fine dust has a smaller average particle size than coarse dust, resulting in higher reactivity with the acidic aqueous solution in the subsequent zinc leaching process, thus improving the efficiency of the zinc leaching reaction.

[0074] In this invention, when using fine dust obtained in the classification process as the iron smelting dust in the zinc leaching process, the average particle size of the fine dust is not particularly limited. However, from the viewpoint that a higher zinc content results in higher reactivity in the zinc leaching process, the average particle size of the fine dust is preferably 100 μm or less, more preferably 20 μm or less, and even more preferably 10 μm or less.

[0075] There are no particular restrictions on the methods used in this classification process. For example, sieves can be used, or the difference in the settling velocity and moving velocity of particles in the fluid (fluid classification) can be used to separate ironmaking dust into coarse and fine dust.

[0076] (Method for preparing an electroplating zinc bath)

[0077] The method for preparing the electroplating zinc bath of the present invention is characterized in that the electroplating zinc bath contains a zinc-containing substance prepared by the above-described method for preparing the zinc-containing substance of the present invention, and the pH of the electroplating zinc bath is 0.5 to 3.5.

[0078] As the zinc source for the electroplating zinc bath used in this invention, in addition to the zinc-containing material of this invention, zinc granules, zinc sulfate (heptahydrate), zinc chloride, and zinc carbonate can be used, for example. Furthermore, as the type of electroplating zinc bath, an acidic bath with excellent productivity is preferred; sulfuric acid baths, chloride baths, and mixtures thereof can be used. Among these, in the chloride bath, since it is necessary to treat the chlorine gas generated when using insoluble anodes, a sulfuric acid bath is more preferred.

[0079] The pH of the electroplating zinc bath should be adjusted to a range of 0.5–3.5, preferably 1.0–3.0. Adjusting the pH to this range suppresses the active generation of hydrogen, which reduces current efficiency, and also inhibits plating burn-in, resulting in a beautiful plating appearance. It is preferable to use an acid appropriate for the type of zinc plating bath used for pH adjustment; for example, if the zinc plating bath is a sulfuric acid bath, sulfuric acid is preferred for pH adjustment.

[0080] There are no particular limitations on the method of using the zinc-containing substance prepared by the method of the present invention as a zinc source in the electroplating zinc bath. For example, a method of adding the zinc-containing substance to an acidic bath obtained by adjusting the zinc source other than the zinc-containing substance and then adjusting the pH can be considered.

[0081] The proportion of zinc-containing material in the zinc source of the electroplating zinc bath is preferably 1.0% by mass or more when converted from all zinc sources. This is because by containing 1.0% by mass or more of zinc-containing material, the cost advantage of the present invention can be fully realized. On the other hand, there is no upper limit to the concentration of zinc-containing material, and the electroplating zinc bath can be prepared using only zinc-containing material as the zinc source.

[0082] The zinc concentration in the electroplating zinc bath is preferably 0.5 mol / L or higher. If the zinc concentration is 0.5 mol / L or higher, there will be no zinc ion deficiency near the steel sheet being plated during electrolysis, which can suppress the formation of charred coating. There is no upper limit to the zinc concentration, but from the viewpoint of processing cost, it is preferably below 2 mol / L.

[0083] In addition, considering the need for temperature stability, the temperature of the electroplating zinc bath is preferably above 30°C. There is no specific upper limit to the temperature of the electroplating zinc bath, but since the evaporation rate of the bath increases with higher temperatures, it is practically preferable to keep it around 90°C.

[0084] Furthermore, conductive additives can be added to the plating bath as needed. This is because it can improve the conductivity of the plating bath. Examples of such conductive additives include sodium sulfate, ammonium sulfate, and potassium sulfate. However, if the amount added increases, the whiteness of the coating may decrease when electrolyzing at a high current density. Therefore, the amount of the conductive additive added is preferably 0.5 mol / L or less.

[0085] As a preferred range for the concentration of impurity elements (Pb, Cd, Fe) in the plating bath, the concentrations of Pb and Cd are preferably 1.0 ppm or less. If the concentration of these impurity elements exceeds 1.0 ppm, the L value of the plating surface may decrease. Additionally, for the same reason, the concentration of Fe is preferably 1000 ppm or less.

[0086] On the other hand, by including inorganic components containing Sn, In, Bi, or Sb, or organic components having a 2-benzothiazole thio group, in the plating bath as needed, electroplated zinc-coated steel sheets with a more aesthetically pleasing surface can be obtained. It is preferable to control these inorganic and organic components within the range of 0.01 to 3 ppm. The form in which these components are added is not particularly limited. The aforementioned inorganic components can be added in a metallic state, or in the form of sulfates, chloride salts, carbonates, oxides, etc., but when using salts, it is preferable to use salts appropriate for the type of electroplating zinc bath. As an organic component having a 2-benzothiazole thio group, 2-mercaptobenzothiazole (MBT) or its salts can be used.

[0087] (Manufacturing method of electro-galvanized steel sheet)

[0088] The method for manufacturing electro-galvanized steel sheet of the present invention is characterized in that the surface of the steel sheet is electro-galvanized using an electro-galvanizing bath prepared by the method for preparing the electro-galvanizing bath of the present invention described above. When manufacturing the electro-galvanized steel sheet, electroplating can be performed after preparing the electroplating bath using zinc-containing substances and zinc sources other than zinc-containing substances such as zinc granules and zinc sulfate. Furthermore, a zinc source including zinc-containing substances prepared by the method for preparing zinc-containing substances of the present invention can be added to the electro-galvanizing bath in the electro-galvanizing steel sheet production line.

[0089] The preferred current density during electrolysis is 10–130 A / dm³. 2 The range is more preferably 10–100 A / dm 2 By setting the current density in electrolysis to 10 A / dm³ 2The above measures prevent a decrease in current efficiency, which could lead to an increase in the time required to ensure the specified plating adhesion. On the other hand, by setting the current density during electrolysis to 130 A / dm³... 2 The following measures can suppress the burning of the coating.

[0090] There are no particular limitations on the type of electrode (anode), but considering the dissolution of impurities in the plating bath, an iridium oxide electrode is preferred. Furthermore, from the viewpoint of reducing the thinning of the diffusion layer at the electrolytic interface, the plating bath flow rate is preferably 1.0 m / s or higher.

[0091] Thus, an electro-galvanized steel sheet is manufactured using an electro-galvanizing bath prepared by the method of the present invention.

[0092] Surface-treated steel sheets can also be produced by forming a chemical conversion coating on the surface of the electro-galvanized steel sheet manufactured as described above. This chemical conversion coating can be formed, for example, by a chromium-free chemical conversion process, i.e., by coating the steel sheet with a chromium-free chemical conversion solution and then heating and drying it at a temperature of 80–300°C without washing it with water. It should be noted that the chemical conversion coating can be a single layer or multiple layers; in the case of multiple layers, multiple chemical conversion treatments can be performed sequentially.

[0093] Furthermore, depending on the intended use of the electro-galvanized steel sheet, a single or multiple layers of coating containing organic resin can be formed on the surface of the plating or chemical conversion treatment film of the electro-galvanized steel sheet manufactured as described above, thus producing a surface-treated steel sheet. Examples of such coatings include polyester resin coatings, epoxy resin coatings, acrylic resin coatings, polyurethane resin coatings, and fluorine resin coatings. Additionally, epoxy-modified polyester resin coatings, obtained by modifying a portion of the aforementioned resins with other resins, can also be used. Furthermore, curing agents, curing catalysts, pigments, additives, etc., can be added to the aforementioned resins as needed.

[0094] There are no specific provisions regarding the coating method used to form the aforementioned coating film, but examples of coating methods include roller coating, curtain coating, and spray coating. For instance, after applying a coating containing organic resin to the surface of an electro-galvanized steel sheet or a chemically converted coating, the coating film can be formed by heating and drying using methods such as hot air drying, infrared heating, or induction heating.

[0095] It should be noted that the above-described method for manufacturing surface-treated steel sheets is an example and is not limited thereto.

[0096] Example

[0097] The following describes embodiments of the present invention, but the present invention is not limited to these embodiments.

[0098] First, zinc is leached into the sulfuric acid solution by adding electric furnace dust (zinc content: 40% by mass, average particle size: 10 μm) as ironmaking dust to a sulfuric acid aqueous solution adjusted to pH 2.0 and stirring for 1 hour (zinc leaching step). Next, the resulting solution is subjected to bath conditioning under various conditions, followed by impurity precipitation treatment (first impurity precipitation step and second impurity precipitation step). Table 1 shows the types of chelating agents, and Table 2 shows the amount of electric furnace dust added, the type of alkaline aqueous solution used to adjust the pH in the first impurity precipitation step, the pH of the pH-adjusted solution, and the type and amount of chelating agent added in the second impurity precipitation step. Additionally, the structural formulas of A1 to A4 shown in Table 1 are also shown. It should be noted that in the impurity precipitation treatment, both the first and second impurity precipitation steps are carried out for 1 hour with stirring after bath conditioning at a solution temperature of 50°C. Then, solid-liquid separation was performed using a suction filter (first solid-liquid separation step). After adjusting the pH of the resulting solution to 9.0 (zinc precipitation step), solid-liquid separation was performed again using a suction filter (second solid-liquid separation step). The resulting solid was dried at 105°C to obtain the zinc-containing substance. It should be noted that the pH adjustment in the zinc precipitation step was performed using an aqueous sodium hydroxide solution. The zinc recovery rate from the electric furnace dust and the proportions of Fe, Cd, and Pb contained in the zinc-containing substance for each No are shown in Table 2.

[0099] [Table 1]

[0100] No Compound Name A1 Sodium dimethyl dithiocarbamate A2 Sodium diethyldithiocarbamate A3 Dipotassium piperazine-1,4-dithiocarbamate A4 pyrrolidine-1-dithiocarbamate ammonium

[0101]

[0102]

[0103] Using the zinc-containing material and zinc sulfate heptahydrate obtained as described above, an electroplating zinc bath was prepared with the zinc concentration adjusted to the concentrations shown in Table 2. Electroplating was then performed under the conditions described below to manufacture electroplated steel sheets. At this time, a 0.7 mm thick cold-rolled steel sheet manufactured using conventional methods was used as the base plate for galvanizing. Test pieces (150 mm × 70 mm) for batch galvanizing were cut from this steel sheet and subjected to degreasing and pickling treatments before electroplating. It should be noted that the zinc coating adhesion per single side was 20 g / m². 2 .

[0104] Electrolysis conditions

[0105] Current density: 50A / dm 2

[0106] Bath temperature: 50℃

[0107] Electrode: Iridium oxide

[0108] Flow velocity: 2.0 m / sec

[0109] In addition, chromium-free chemical conversion treated steel sheets are produced by coating the plating surface of the obtained electro-galvanized steel sheets with epoxy resin (manufactured by JAPAN EPOXY RESIN (Co., Ltd., trade name: jER1009).

[0110] The obtained electro-galvanized steel sheets and chromium-free chemical conversion treated steel sheets were tested for brightness (L value) according to JIS Z8722:2009 using a spectrophotometer (NDS SD5000, manufactured by Nippon Denshoku Kogyo Co., Ltd.) via SCE (stripping of positive reflections). For electro-galvanized steel sheets, L values ​​of 80 or higher were rated ◎, 76 or higher but less than 80 were rated 〇, and less than 76 were rated ×. For chromium-free chemical conversion treated steel sheets, L values ​​of 60 or higher were rated ◎, 56 or higher but less than 60 were rated 〇, and less than 56 were rated ×. It should be noted that ◎, 〇, and × represent the degree of goodness, respectively.

[0111] Table 2 shows a comparison between electro-galvanized steel sheets treated without the first and second impurity precipitation processes and chromium-free chemical conversion treated steel sheets. It can be seen that the zinc-containing material contains a large number of impurities, resulting in a high impurity concentration and a low L value in the electro-galvanizing bath. Table 2 shows a comparison with only the first impurity precipitation process. Although the Fe ratio in the zinc-containing material is reduced, Cd and Pb remain, resulting in a higher Cd and Pb concentration and a lower L value in the electro-galvanizing bath. Table 2 shows a comparison with only the second impurity precipitation process. Due to the low pH, the chelating agent decomposes, resulting in the same high impurity ratio in the zinc-containing material as in Table 2. Consequently, the impurity concentration in the electro-galvanizing bath is also higher, and the L value is also lower. Table 2 shows a comparison with the pH being below the lower limit during the first impurity precipitation process. Although the Fe ratio in the zinc-containing material is reduced, the low pH causes the chelating agent to decompose, leaving Cd and Pb residues in the zinc-containing material, resulting in a low L value. Comparative example No. 5 shows that the pH exceeded the upper limit in the first impurity precipitation process, resulting in a significant decrease in zinc recovery. Therefore, it is not suitable as a zinc source for electroplating. Comparative example No. 6 shows that the chelate addition was below the lower limit, but it is evident that the Cd and Pb ratios in the zinc-containing material were not sufficiently reduced, and the L value was also low.

[0112] On the other hand, as can be seen from the invention examples No.7 to 22, the proportions of Fe, Cd, and Pb can be reduced without significantly reducing the Zn concentration of zinc-containing substances, and the concentration of impurities in the electroplating zinc bath is also sufficiently low, thus the L value shows a high value.

[0113] Examples No. 23 and No. 24 are embodiments where the proportion of the zinc-containing material to the zinc source in the electroplating bath is 1.1% by mass, which is close to the lower limit of the preferred range of the present invention. No. 23 is a comparative example prepared without the first and second impurity precipitation processes. Due to the influence of impurities contained in the zinc-containing material, the impurity concentration in the electroplating bath exceeds the allowable range, resulting in a low L value. On the other hand, regarding the inventive example No. 24, which includes the first and second impurity precipitation processes, it is known that the proportions of Fe, Cd, and Pb in the electroplating bath can be reduced, and a high L value is also observed. Furthermore, No. 25 is an inventive example where only the zinc-containing material is used to adjust the electroplating bath; since the proportions of Fe, Cd, and Pb in the zinc-containing material are sufficiently low, the impurity concentration in the electroplating bath is also low, resulting in a high L value. Additionally, No. 26 is an inventive example in which MBT is added to the inventive example No. 10; compared to No. 10 without MBT, the L value is increased.

[0114] Industrial availability

[0115] According to the present invention, a zinc-containing material made from iron smelting dust can be provided for use in manufacturing electroplated galvanized steel sheets with a beautiful and bright appearance.

Claims

1. A method for preparing a zinc-containing substance, characterized in that, It includes the following processes: The zinc leaching process involves contacting iron smelting dust with an acidic aqueous solution, thereby leaching the zinc contained in the iron smelting dust into the acidic aqueous solution. In the first impurity precipitation step, impurities are precipitated when the pH of the first treatment solution obtained in the zinc leaching step is 4.0 to 6.

0. In the second impurity precipitation step, a chelating agent of 0.10 g / L or more is added to the second processed solution obtained in the first impurity precipitation step at a pH of 4.0 to 6.0 to precipitate the impurities. The first solid-liquid separation process involves performing solid-liquid separation on the third processed liquid obtained in the second impurity precipitation process. In the zinc precipitation process, zinc-containing substances are precipitated in the fourth treatment solution obtained in the first solid-liquid separation process at a pH of 8.0 to 12.0; and The second solid-liquid separation process separates the fifth treatment liquid obtained in the zinc precipitation process into zinc-containing substances and residual liquid.

2. The method for preparing the zinc-containing substance according to claim 1, wherein, The zinc leaching process further includes a grading process that separates iron smelting dust into coarse dust and fine dust, and the fine dust obtained in the grading process is used as the iron smelting dust in the zinc leaching process.

3. The method for preparing the zinc-containing substance according to claim 1 or 2, wherein, In the second impurity precipitation step, at least one of the chelating agents added to the second treatment solution is a chelating agent that forms a chelate with at least one of Cd and Pb.

4. The method for preparing the zinc-containing substance according to any one of claims 1 to 3, wherein, In the second impurity precipitation step, at least one of the chelating agents added to the second treatment solution is a compound having the structure shown in general formula (I), wherein R 1 and R 2 M indicates a substituted alkyl group. + Indicates a monovalent cation.

5. A method for preparing an electroplating zinc bath, characterized in that, The electroplating zinc bath contains a zinc-containing substance prepared by the method of any one of claims 1 to 4, and the pH of the electroplating zinc bath is 0.5 to 3.

5.

6. A method for manufacturing an electro-galvanized steel sheet, characterized in that, Electro-galvanized steel sheet is manufactured by electro-galvanizing the surface of a steel sheet using an electro-galvanizing bath prepared by the method described in claim 5.

Citation Information

Patent Citations

  • Zinc separation method, zinc material production method and iron material production method

    JP2022105980A